The Concept of Environmental Ecology in QS. Al-Mu'minun Verse 18: The Antics of Roland Barthes Semantic Linguistic Studies - Assamarqondi, Labib Maftuh; Musolli, Musolli (JURNAL ISLAM NUSANTARA, 2023)
This study explores the environmental ecology concept implied in verse 18 of Surat Al-Mu'minun (QS. Al-Mu'minun. This study uses a semantic linguistic approach concerning Roland Barthes' theory in analyzing the meaning of the Qur'anic text. The analysis method involves reconstructing and understanding the meaning of keywords in the verse. The results revealed that verse 18 of Surat Al-Mu'minun reflects relevant ecological thinking related to man's responsibility toward the universe in Islam. Through Roland Barthes' semiotic analysis, the meaning of connotation and denotation was found. The meaning of the denotation is the text itself: "And We sent down water from heaven by a measure". While the meaning of the connotation is that water falling from the sky is rain, and with a measure, it means that humans cannot use it excessively. The concept of ecology in this verse includes aspects of protection and management of nature and ecosystem balance. This research provides insight into how the teachings of the Quran reflect environmental awareness and social responsibility in preserving the universe.